Urdu Translation and Psychometric Evaluation of Core Self-Evaluation Scale for Adolescents - Zubash Aslam; *Dr. Shazia Habib (Review Journal of Social Psychology & Social Works, 2025)
Core Self-evaluation (CSE) is a higher-order construct comprising broad and evaluative features, such as generalized self-efficacy and self-esteem, collectively representing people's fundamental assessments of their worth and ability (Judge et al., 1998). This study aimed to translate and validate the 12-item Core Self Evaluations Scale (CSES; Judge et al., 2003) for adolescents. In the study's initial phase, the Core Self-Evaluation scale was translated into Urdu by following the International Testing Commission (ITC, 2019) standards. The findings of the study indicated that Cronbach's alpha was excellent (α=.90). Additionally, there was a strong inter-correlation between the scores on the CSES forward, backward and Urdu translations ranging from .88 to .92. Based on the original criteria for model fit, i.e., item loading >.35, a confirmatory factor analysis was carried out with 300 adolescent sample to investigate the original model with a two-factor structure (Positive and Negative core self-evaluations) that demonstrated a good fit for the data with six items in each subscale. The items' factor loadings varied from .33 to .89. Negative CSES shows higher AVE, while Positive CSES remains distinct per Fornell and Larcker’s (1981) criterion. High composite reliability confirms its convergent validity. In conclusion, the CSES was shown to have excellent psychometric features, and CFAs helped identify a model that fits well. The CSES is correlated with various health-related factors like pain, fearfulness, sadness, and subjective well-being, and it is a good prospect for research and screening tools in the fields of clinical and health psychology in addition to industrial and organizational psychology.